Parâmetros metabólicos de ratos propensos a demonstrarem corrida selvagem devido a crises audiogênicas e brigas induzidas por privação de sono REM - Moraes, Gabriel Parmezani [UNESP]; Rafacho, Alex [UNESP]; Bosqueiro, José Roberto [UNESP]; Hoshino, Katsumasa [UNESP]; de Paula, Hugo Medeiros Garrido (My University, 2010)
Objective: Total sleep or selective REM-sleep deprivation (SD) increases aggressiveness. Rats that display fighting when submitted to sleep-deprivation are those that manifest wild running (WR), a panic-like flight that precedes tonic-clonic seizures induced by intense acoustic stimulation (audiogenic epilepsy). The incidence of WR-sensitive rats in the colonies around the world may reach 20%, which makes important to know the other characteristics of these animals for both sleep and other kinds of experimental research. Based on the report of their reduced body weight, we investigated some glucose metabolism parameters. Methods: Adult male Wistar rats were submitted to high-intensity acoustic stimulation (112dB, 60s) and then classified as WR-sensitive or WR-resistant rats. Glycemia and insulinemia, measured by glucometer and radioimmunoassay, respectively, and body weight were analyzed during three months. At the end of this period, intraperitoneal glucose and insulin tolerance tests were performed, and hepatic fat and glycogen content were also determined. Results: WR-sensitive rats showed proportionally less gain of body mass compared to the resistant ones (p<0.05) in initial measurements, but this tendency did not sustain thereafter. Interestingly, fasting glycemia was significantly lower in the WR-sensitive group throughout the experiment, compared to WR-resistant rats. No significant differences between groups were found in insulinemia, peripheral glucose and insulin tolerance, and hepatic glycogen. However, WR-sensitive rats increased hepatic fat content significantly after a 12-hour fasting. Conclusions: Slow weight gain, decreased fasting glycemia and hepatic steatosis suggest a possible accelerated energetic metabolism or low resistance to food deprivation, which could partially explain the reduced body weight of WR-sensitive rats.
Metabolic parameters of rats prone to display wild-running of the audiogenic crisis and fights induced by REM-sleep deprivation
Keywords: Acoustic stimulation; Adipose tissue/metabolism; Aggression; Animals; Blood glucose/metabolism; Body weight; Energy metabolism/physiology; Epilepsy; Lactic acid/blood; Metabolism; Panic/physiology; Rats; Reflex/physiopathology; Running; Seizures/metabolism; Sleep deprivation; Sleep deprivation/physiopathology; Wistar